From wheat bran to equine gut: the in vitro fermentation dynamics of aleurone - Boshuizen, Berit; Willems, Maarten; De Maré, Lorie; Hosotani, Guilherme; De Oliveira, Jean Eduardo; Horemans, Benjamin; Vidal Moreno De Vega, Carmen; Verdegaal, Elisabeth-Lidwien J. M. M.; Delesalle, Catherine (Frontiers in Physiology, 2025)
IntroductionAleurone, a bioactive wheat bran component, has been shown to modulate host metabolism and gut microbiota, but its effects across different compartments of the equine gastrointestinal (GI) tract remain unclear. In this study, we aimed to characterize aleurone-derived metabolite profiles using an in vitro fermentation model with digesta from three equine GI compartments (jejunum, cecum, and colon).MethodsThree substrates (control feed, aleurone-containing feed, and pure aleurone) were fermented over 72 h, and targeted metabolomics was performed on 38 metabolites.ResultsSignificant substrate- and compartment-dependent effects were found for 21 metabolites. Aleurone-containing feed increased asparagine and threonine levels while reducing lactic acid, particularly in the cecum. In contrast, control feed showed the highest overall metabolite abundance, suggesting greater microbial accessibility. Time-resolved analyses revealed dynamic production–utilization patterns; isoleucine, for example, displayed a distinct peak–decay pattern in the colon. Carnitine increased over time across compartments, showing local production, especially in the cecum. Artificial intelligence-based classification models achieved >90% accuracy in distinguishing substrate types and revealed ferulic acid and indole acetic acid as key differentiators.DiscussionThe findings suggest that aleurone’s structural matrix may influence metabolite release and microbial access, highlighting its functional role in modulating fermentation and overall host metabolism. In this study, we demonstrate that aleurone alters microbial fermentation and metabolite output in a time- and compartment-specific manner. These insights enhance our understanding of aleurone as a functional feed component in horses and provide a foundation for future dietary strategies targeting metabolic and gut health.